2007
DOI: 10.1002/hipo.20356
|View full text |Cite
|
Sign up to set email alerts
|

Differential involvement of the dorsal hippocampus in passive avoidance in C57bl/6J and DBA/2J mice

Abstract: The inferior performance of DBA/2 mice when compared to C57BL/6 mice in hippocampus-dependent behavioral tasks including contextual fear conditioning has been attributed to impaired hippocampal function. However, DBA/2J mice have been reported to perform similarly or even better than C57BL/6J mice in the passive avoidance (PA) task that most likely also depends on hippocampal function. The apparent discrepancy in PA versus fear conditioning performance in these two strains of mice was investigated using an aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(75 citation statements)
references
References 52 publications
4
71
0
Order By: Relevance
“…Finally, we examined associative memory in the passive avoidance task, based on the association formed between an aversive stimulus (electrical foot shock) and a specific environmental context (light-dark) ( Figure 4D), which relies on cortical and hippocampal circuits (48)(49)(50). Latency to step-through during the training session was found to be similar between genotypes.…”
Section: Increased P75mentioning
confidence: 99%
“…Finally, we examined associative memory in the passive avoidance task, based on the association formed between an aversive stimulus (electrical foot shock) and a specific environmental context (light-dark) ( Figure 4D), which relies on cortical and hippocampal circuits (48)(49)(50). Latency to step-through during the training session was found to be similar between genotypes.…”
Section: Increased P75mentioning
confidence: 99%
“…This is because we observe a loss of memory precision in both the contextual fear task as well as novel object recognition and novel object location tasks in GABA B(1a) knockout mice. Both of these novel object tasks are independent of fear responses and rely heavily on hippocampal functioning (Best and Orr 1973;Lorenzini et al 1996;Ambrogi Lorenzini et al 1997;Baarendse et al 2007). Moreover, dysfunction of presynaptic inhibition and synaptic potentiation within the mossy fiber pathway and Schaffer commissural pathway is well documented in these mice (Vigot et al 2006;Guetg et al 2009;Gassmann and Bettler 2012), as is the importance of the mossy fiber pathway in memory precision (Ruediger et al 2011;Jasnow et al 2012).…”
mentioning
confidence: 99%
“…D2 and DBF 1 mice showed no significant differences in night and total activities of males, and in max for 15 min. For the percent of night activity, D2 showed significantly higher values than B6 or DBF 1 (Table 2).…”
Section: Resultsmentioning
confidence: 98%
“…For PA performance, D2 mice were the worst learners among the groups at both shock intensities for males and at 0.3 mA for females, whereas B6 mice were the worst learners at 0.15 mA for females in this study. Some previous studies also indicate that D2 mice are poorer performers than B6 mice [1,29], although one study has indicated that the performance of B6 was poorer than that of D2 mice [18]. These inconsistent results for strains in the PA test may arise from differences in experimental conditions such as shock intensity [25].…”
Section: Discussionmentioning
confidence: 97%